Creative Thinking Ability With Open-Ended Problems Based on Self-Efficacy in Gnomio Blended Learning - Ulinnuha, Rais; Budi Waluya, St.; Rochmad, Rochmad (Unnes Journal of Mathematics Education Research, 2021)
This study aims to describe the mathematical creative thinking abilities based on mathematics self-efficacy of 8th grade students. The type of this study was a mixed method. The design of this study was sequential explanatory. The population of this study was 8th grade of SMPN 3 Temanggung which consisted of six classes. The data collecting techniques based on self-efficacy were taken 2 subjects for each category in a purposive manner. The result showed that the description learning of mathematical creative thinking abilities based on mathematics self-efficacy varied. This was showed from 3 students with high self-efficacy, 2 students obtained mathematical creative thinking abilities in the high category and 1 student in the moderate category. From 24 students with moderate self-efficacy, 6 students obtained mathematical creative thinking abilities in the high category, 13 students in the moderate category, and 5 students in the low category. From 5 students with low self-efficacy, 1 student obtained mathematical creative thinking abilities in the high category, 2 students in the moderate category, and 2 students in the low category.